KAJIAN KRIMINOLOGI KORUPSI DI SEKTOR PUBLIK DI INDONESIA - Tampubolon, Patar; L. Panggabean, Mompang; Tampubolon, Manotar (CV. Lafadz Jaya, 2024)
This qualitative study investigates the criminology of corruption within Indonesia's public sector, employing the Behavioral Crime Theory, Rational Choice theory, and Social Learning theory as theoretical frameworks. Drawing upon secondary data from reputable sources such as books and journals, the study aims to achieve several objectives: first, to understand the behavioral patterns underlying corrupt activities among public officials; second, to analyze the rational decision-making processes that lead individuals to engage in corrupt practices; and third, to explore the role of social learning mechanisms in perpetuating corrupt behavior within the public sector. The study hypothesizes that the low level of sanctions, coupled with the preference for corruption due to perceived benefits and the inadequate conditions of incarceration, contribute to the persistence of corruption in Indonesia's public sector. Findings indicate a correlation between lenient legal consequences, personal preference for corruption, and the state of correctional facilities, highlighting the need for comprehensive reforms in both legal enforcement and penal institutions. Recommendations include strengthening anti-corruption laws, enhancing penalties for corrupt activities, fostering a culture of integrity through education and awareness, and improving the conditions of imprisonment to serve as a deterrent against corrupt behavior. This research contributes to the understanding of corruption dynamics in the public sector and provides insights for policymakers and law enforcement agencies to combat this pervasive societal issue effectively.